Impact of Fungicide on Wheat - G. F. Sassenrath; H. Zhao; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2021)
This is a report of research to test the impact of fungicide and management on wheat yield and quality. Fusarium head blight (FHB), or scab, is a persistent problem in wheat production, especially in high rainfall areas such as eastern Kansas. Two cultivars of winter wheat varying in FHB sensitivity (Everest, moderately resistant, and KanMark, susceptible) were tested for control of FHB using fungicide treatments made to the seed prior to planting or to the wheat plant at heading, in tilled or no-tilled management. The wet spring of 2020 resulted in high FHB pressure, but dry conditions at harvest reduced contamination. Tillage had a larger impact on yield improvement than fungicide applications in 2020. Tillage also impacted test weight and protein content.
Keywords: winter wheat; fungicide; Fusarium Head Blight; fungal disease; soil microbial activity; wheat protein